The Impact of Intelligence Quotient On The Learning Outcomes of Musical Art in State Schools - Isnain, Zakaria (Universitas Negeri Semarang, 2021)
This study aims to determine, describe and analyze the impact of intelligence quotient on learning outcomes in the musical art. This research was conducted on student representatives with a total sample of 324 students. The method used in this study was a quantitative method with an ex post de facto approach and correlational design. The data collection techniques used a psychological scale in the form of intelligence quotient tests, documents on the results of learning musical art and interviews with student representatives. The data analysis technique used was a simple linear regression test with the Best Linear Unbiased Estimated standard. The results showed that there is a significant and positive impact of intelligence quotient on the learning outcomes of musical art with the contribution percentage of 16.1% and 83.9% influenced by other factors that are not part of the research variables. Based on the results of the analysis and discussion, the researchers hope that this research can (1) facilitate students in getting new insight and experience related to intelligence quotient tests, (2) be a guide for teachers in understanding the conditions related to students' intellectual abilities, (3) be material considerations of art education teachers in designing intellectual-based learning and (4) be the basis for developing intelligence quotient tests. The suggestions from the researchers are certainly addressed to many parties, education implementers for the government, schools, teachers, further researchers and students.